A new large hypercarnivorous crocodyliform from the Maastrichtian of Southern Patagonia, Argentina - Fernando E. Novas; Diego Pol; Federico L. Agnolín; Ismar de Souza Carvalho; Makoto Manabe; Takanobu Tsuihiji; Sebastián Rozadilla; Gabriel L. Lio; Marcelo P. Isasi (PLoS ONE, 2025)
The first crocodyliform specimen from the Maastrichtian Chorrillo Formation (Austral Basin, Patagonia) is here described. The discovery was made about 30 km to the SW of the town of El Calafate (Province of Santa Cruz, Argentina) and consists of a beautifully preserved and articulated skull and jaws, and part of the postcranial skeleton that were preserved encased in a large concretion. This new taxon belongs to the notosuchian clade Peirosauridae, representing the latest and southernmost record for this group of crocodyliforms. The new taxon is recovered as closely related to other robust and broad-snouted peirosaurids that lived by the end of the Cretaceous Period, such as Colhuehuapisuchus from the Maastrichtian of Central Patagonia and Miadanasuchus oblita from the Maastrichtian of Madagascar. The completeness of the new specimen reveals, for the first time, the anatomy and body plan of a large and broad snouted peirosaurid. The new taxon bears large ziphodont teeth, a broad oreinirostral snout that is only slightly longer than 50% the skull length, and a deep adductor chamber in the temporal region and posterior mandibular ramus. The anterior region of its postcranial skeleton is preserved and shows broad scapula and a robust humerus features previously known in large predatorial notosuchians. The new crocodyliform adds to the predatorial component of terrestrial ecosystems at high paleolatitudes by the end of the Cretaceous Period.